Ventricular Tachycardia Originating from Moderator Band: New Perspective on Catheter Ablation - Jin-yi Li; Jing-bo Jiang; Yan He; Jian-chun Luo; Guo-qiang Zhong (Case Reports in Cardiology)
A 59-year-old woman was referred to the institution with burdens of idiopathic ventricular tachycardia (IVT). Electroanatomic mapping revealed a complex fractionated, high frequency potential with long duration preceding the QRS onset of the IVT. The real end point of ablation was the disappearance of the conduction block of Purkinje potential during the sinus rhythm besides the disappearance of the inducible tachycardia. Location of distal catheter was at the moderator band (MB) by transthoracic echocardiography (TTE). Only irrigated radiofrequency current was delivered at both insertions of the MB which can completely eliminate the IVT.